Phylogenetic analysis of the microbial mat in the hot spring Garga (Baikal rift zone) and the diversity of natural peptidases - E. V. Lavrentyeva; A. A. Radnagurueva; T. G. Banzaraktsaeva; S. M. Bazarov; D. D. Barkhutova; I. D. Ulzetueva; M. K. Chernyavsky; M. R. Kabilov; V. V. Khakhinov (Вавиловский журнал генетики и селекции)
Hydrolytic bacteria (in particular, proteolytics) are the primary destructors in hot springs. The proteolytic bacteria are able to secrete enzymes that are active in wide ranges of pH and temperature. The aim of this work was to study the taxonomic composition, the structure of the bacterial microbial mat, and to study the distribution of peptidases in the thermophilic microbial Garga community. For the study, we sampled the microbial mat at a water temperature of 54.2 °C and a pH of 8.3. Hydrochemical analysis of water showed a high content of sulfates, 390 mg/dm3. The microelement composition of water showed that the Garga water had increased concentrations of B, Rb, Li, Ba, Sr. We analyzed the taxonomic diversity of the microbial community in the hot spring Garga at a temperature zone of 54 °C. The structure of the microbial mat is represented by various phylogenetic groups of mesophilic and thermophilic bacteria, with various metabolic and ecological functions. The dominant group in this community was the phylum Firmicutes (64 %). The analysis of the collected metagenomic sequences of the microbial community allowed the detected peptidases in the microbial community in the hot spring Garga to be for the first time systematized and characterized. Comparisons of metagenomic sequences of representative data showed a dominance of serine peptidase class enzymes. Natural peptidases in the investigated microbial community ensure the hydrolysis of biopolymers at the first stages of the destruction of organic matter and may have biotechnological relevance.